Unraveling the Man: Toxic Masculinity and Cowboy Culture in ‘The Power of the Dog’ - Ardi Nugroho; Wandi Wijaya (JADEs Journal of Academia in English Education, 2024)
This research explored how language, dialogue, and character portrayal in Jane Campion's 2021 film "The Power of the Dog" contributed to the deconstruction of toxic masculinity within the traditional cowboy film genre. Having won several awards, the movie is considered to be a suitable source of data for the current study, especially since it explores the theme of toxic masculinity to some extent. Employing a discourse analysis approach to examine the film's dialogue, clothing, and character interactions, this study revealed how the film challenged stereotypical notions of masculinity associated with strength, stoicism, and dominance. By analyzing specific scenes involving characters like Phil Burbank, the research demonstrated how the film critiqued the emotional repression and violence often linked to cowboy culture. The results also revealed how toxic masculinity and cowboy culture are related and mutually strengthen and maintain the construction of both. This exploration contributed to the understanding of how contemporary films could challenge traditional gender norms and redefine masculinity.